2004
DOI: 10.1099/jmm.0.05497-0
|View full text |Cite
|
Sign up to set email alerts
|

Chlorate: a reversible inhibitor of proteoglycan sulphation in Chlamydia trachomatis-infected cells

Abstract: Sulphated glycosaminoglycans, such as heparan sulphate, have been shown to be essential for the infectivity of many organisms. The aims of this study were to verify the role of sulphated glycosaminoglycans in chlamydial infection and to investigate whether they are present on chlamydia or chlamydial host cells. The effect of undersulphation of host cells and chlamydial elementary bodies was examined using sodium chlorate. Also studied was whether any inhibitory effect was reversible. The results strongly sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 11 publications
2
15
1
Order By: Relevance
“…The ∼5% of heparan sulfate remaining in the SLC35B2 clone may be due to activity of the second PAPS transporter (PAPST2). Chlorate is a competitive inhibitor of PAPS synthetase and blocks sulfation, which partially protects host cells from Chlamydia infection (31). However, the high concentrations of chlorate required to block Chlamydia infection are toxic to the host cells.…”
Section: Discussionmentioning
confidence: 99%
“…The ∼5% of heparan sulfate remaining in the SLC35B2 clone may be due to activity of the second PAPS transporter (PAPST2). Chlorate is a competitive inhibitor of PAPS synthetase and blocks sulfation, which partially protects host cells from Chlamydia infection (31). However, the high concentrations of chlorate required to block Chlamydia infection are toxic to the host cells.…”
Section: Discussionmentioning
confidence: 99%
“…As serovar E binding has been reported to be variably sensitive to heparan sulfate [27], [57], [58], we investigated the role of the FGF2 pathway during epithelial cell infection. We first tested whether FGF2 can enhance serovar E binding to HeLa cells.…”
Section: Resultsmentioning
confidence: 99%
“…Although Western blot analysis indicated a reduction in total PARP protein levels with chlorate, production of the cleaved PARP fragment, a definitive indicator of apoptosis, was not observed in every sample (data not shown). A conservative dose of 30 mM chlorate was used in all remaining assays as it achieved significant reductions in cell number without significant increases in cytotoxicity, and was within doses used on other cell types (Fadel and Eley 2004;Yip et al 2002;Zertal-Zidani et al 2007;Zou et al 2004). The effectiveness of this dose was also reflected in its ability to up-regulate ALP activity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the context of the current study, TAT-EGFP treatment has indicated chlorate treatment of MG-63 cells as an appropriate method to further analyse the importance of GAGs in osteogenic systems. This method may also be advantageous in the identification of new drugs and treatments capable of altering GAG expression and may be of particular benefit in the development of treatments against pathogens which use cell surface GAGs in their cell invasion process (Carruthers et al 2000;Fadel and Eley 2004;McCormick et al 2000). TAT-PTD transduction could also be helpful in deciphering the paradoxical ability of GAGs to both promote and inhibit tumour progression (Ford et al 2001;Wu 2006).…”
Section: Discussionmentioning
confidence: 97%